2022
DOI: 10.1155/2022/3841161
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 Genes and Carbapenem-Hydrolyzing Class D β-Lactamases (CHDLs) in Clinical Isolates of Pseudomonas aeruginosa Collected from West of Iran, Hamadan

Abstract: Carbapenem-hydrolyzing class D β-lactamases (CHDLs) are on the rise and are a major public health problem worldwide. Pseudomonas aeruginosa is resistant to carbapenem; currently, the most effective treatment option is being increasingly reported. This study aimed to identify blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 genes in CHDL strains. Samples were collected from clinical specimens admitted to the hospital. Antibiotic susceptibility was determined using the disk diffusion methods. CHDL strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…bla SHV is recognized as the most prevalent ESBL gene that confers antibiotic resistance to pathogenic bacteria worldwide, primarily in E. coli and Klebsiella spp. [28][29][30][31], whereas bla OXA is typically identified in Pseudomonas aeruginosa [32] and Acinetobacter baumannii [33]. However, R. ornithinolytica harboring bla SHV and bla OXA has been isolated from a patient in China [34].…”
Section: Discussionmentioning
confidence: 99%
“…bla SHV is recognized as the most prevalent ESBL gene that confers antibiotic resistance to pathogenic bacteria worldwide, primarily in E. coli and Klebsiella spp. [28][29][30][31], whereas bla OXA is typically identified in Pseudomonas aeruginosa [32] and Acinetobacter baumannii [33]. However, R. ornithinolytica harboring bla SHV and bla OXA has been isolated from a patient in China [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that the presence of the blaOXA-4 gene is significantly associated with resistance to cefepime. In a study in Hamadan, Iran, Sezadehghani et al identified frequency carbapenem encoding genes (OXA), including blaOXA-145 (27.5%), blaOXA-224 (22.0%), blaOXA-539 (20.1%), and blaOXA-675 (11.9%) in clinical isolates of P. aeruginosa, which exhibited MDR (30). In a study by Radmehr et al in North Khorasan, Iran, the frequency of blaOXA-23 gene was reported 61.42% (31).…”
Section: Discussionmentioning
confidence: 99%
“…30 Based on research by Sezahdeghani, et al, P. aeruginosa isolates were 40.3%, 43.1%, and 44.9% resistant to meropenem, ertapenem, and imipenem, respectively. 31 Carbapenemases are βlactamases and include serine-β-lactamases (KPC, OXA, and GES genes) and metallo-β-lactamases (MBL). Approximately 15.5% of the isolates produced strong biofilms, 37.6% of the isolates produced moderate biofilms, and 10.2% of the isolates produced weak biofilms.…”
Section: Biofilm Formationmentioning
confidence: 99%